Fit for Industry 4.0 : innovative learning and teaching for digitalization and automation - Spöttl, Georg [Verfasser]; Parvikam, Siriporn [Verfasser]; Paryono, Paryono [Verfasser] (wbv Media GmbH & Co. KG, 2021)
"This volume presents a further training concept on Industry 4.0 for vocational teachers, which was developed for transnational use by the "Gesellschaft für Internationale Zusammenarbeit" (GIZ) together with SEAMEO VOCTECH (Regional Centre for Vocational and Technical Education and Training) and ASEAN (Association of Southeast Asian Nations) for transnational use. In connection with the thematic focus on digitalisation and the accompanying change in the world of work, innovative teaching and learning methods for self-reliant learning and the promotion of communicative and social competences are presented. In the transfer project, the professional and didactical competences of teachers and trainers are promoted." (Publisher, BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.3 Wandel von Arbeit & Wirtschaft; P 3.2 Lehrpersonal; I 2.3.4 Asien; 370; Digitalisierung; Industrie 4.0; Arbeitsmarkt; Zukunft der Arbeit; Berufsbildung; Qualifikationsanforderung; Lehrerbildung; Ausbilder; Trainingsprogramm; Südostasien; Learning Analytics